Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.jid.2017.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide MicroRNA Analysis Implicates miR-30b/d in the Etiology of Alopecia Areata

Abstract: Alopecia areata (AA) is one of the most common forms of human hair loss. Although genetic studies have implicated autoimmune processes in AA etiology, understanding of the etiopathogenesis is incomplete. Recent research has implicated microRNAs, a class of small noncoding RNAs, in diverse autoimmune diseases. To our knowledge, no study has investigated the role of microRNAs in AA. In this study, gene-based analyses were performed for microRNAs using data of the largest genome-wide association meta-analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In AA, three genome‐wide association studies showed that 12 independent genetic loci, including loci encoding genes in both innate and adaptive immunity, are involved. In particular, among the HLA class II genes, the DR4, DR5, DQ3, DQ7, and DPW4 alleles are strongly associated . Similarly, MS shows strong association with more than 100 polymorphisms; most of them are related to immune function genes, particularly linked to the major histocompatibility complex (MHC) II allele HLA‐DR2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In AA, three genome‐wide association studies showed that 12 independent genetic loci, including loci encoding genes in both innate and adaptive immunity, are involved. In particular, among the HLA class II genes, the DR4, DR5, DQ3, DQ7, and DPW4 alleles are strongly associated . Similarly, MS shows strong association with more than 100 polymorphisms; most of them are related to immune function genes, particularly linked to the major histocompatibility complex (MHC) II allele HLA‐DR2 …”
Section: Discussionmentioning
confidence: 99%
“…In particular, among the HLA class II genes, the DR4, DR5, DQ3, DQ7, and DPW4 alleles are strongly associated. 10,11 Similarly, MS shows strong association with more than 100 polymorphisms; most of them are related to immune function genes, particularly linked to the major histocompatibility complex (MHC) II allele HLA-DR2. 12 Another common aspect between AA and MS concerns the environmental factors that may cause the onset of the autoimmune activation.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of AA pathogenesis has advanced significantly, though it still has many gaps. Today, AA research is active in genetics, the microbiome, the role of the environment, the role of atopy, immune cell types in AA pathogenesis, primary antigenic targets, mechanisms by which immune cells influence hair follicles, and of course the development of new treatments based on these discoveries. This increased AA research activity (Figure ), from a larger number of professionals, promises momentous developments to come!…”
Section: Alopecia Areata Research In the Modern Agementioning
confidence: 99%
“…in particular, among the Hla class ii genes the dr4, dr5, dQ3, dQ7 and dPW4 alleles are strongly associated. 17,18 interestingly an increased risk for autoimmune type…”
Section: Associated Diseasesmentioning
confidence: 99%